SISTEM PENDUKUNG KEPUTUSAN UNTUK PENYELEKSIAN CALON PENERIMA BANTUAN PROGRAM INDONESIA PINTAR MENGGUNAKAN SIMPLE ADDITIVE WEIGHTING - Sherly Christina; Enny Dwi Oktaviyani; Licantik Licantik; Jen Paolo Encun; Deddy Ronaldo (Jurnal Teknologi Informasi: Jurnal Keilmuan dan Aplikasi Bidang Teknik Informatika, 2022)
The "Program Indonesia Pintar" (PIP) is a program from the Indonesian government to help children from poor families to get the proper education. Schools often deal with obstacles when selecting the students who are eligible for the PIP grant, due to the process of collecting and managing many registration files, thus requiring high accuracy to prevent errors in the selection results. Therefore, this research aims to develop a website of Decision Support System to support the tasks of the PIP recipient selection committee. The Decision Support System applies the Simple Additive Weighting (SAW) method to obtain the selection results from the ranking of the requirements data handed over by the applicants for the selection of PIP beneficiaries. Then this research applies the Waterfall software development method to analyze, design and develop the Decision Support System website. Furthermore, the results of the black box test indicate that the functions of this Decision Support System work according to their objectives. The system can manage the selection registration data and generate the rankings of prospective PIP beneficiaries.